PENGGUNAAN POC PAITAN (Thitonia diversifolia L.) DAN PUPUK GANDASIL D PADA BUDIDAYA SAWI HIJAU (Brassica juncea L.) SECARA HIDROPONIK - Marzuki Imran; Mardaleni (UIR Press, 2025)
The use of POC paitan (Tithonia diversifolia L.) and Gandasil-D fertilizer in the hydroponic cultivation of green mustard greens (Brassica juncea L.) aims to determine the interaction and main effects of the concentration of POC paitan and the dosage of Gandasil-D fertilizer. This research was carried out at the Integrated Experimental Agriculture Unit, Faculty of Agriculture, Riau Islamic University, Jalan Kasang Kulim Teropong, Kubang Raya Village, Siak Hulu District, Kampar Regency. The research was conducted from June to July 2024. The design used in this research was a factorial Split-Plot Design (RPT) with two factors. The first factor is POC paitan, with four treatment levels: 0, 300, 600, and 900 ppm. The second factor is the dose of Gandasil-D fertilizer, with four treatment levels (0, 5, 10, and 15 g/l), resulting in 16 treatment combinations with three replications, meaning there are 48 experimental units. The parameters observed were plant height, number of leaves, leaf area, economic wet weight, dry weight, root volume, and leaf chlorophyll. The observation data were analyzed statistically, and the BNJ test was performed at the 5% level. The results showed that the interaction and main effects of the POC paitan dose and the Gandasil-D fertilizer dose had a significant impact on plant height, number of leaves, dry weight, root volume, and leaf chlorophyll, but had no significant effect on leaf area and economic wet weight. The best treatment was a combination of POC paitan at 900 ppm and Gandasil-D at 15 g/l.